A new T-circuit model of wind turbine generator for power system steady state studies - Rudy Gianto; Kho Hie Khwee (Institute of Advanced Engineering and Science, 2021)
Modeling of wind power plant (WPP) is a crucial issue in power system studies. In this paper, a new model of WPP for steady state (i.e. load flow) studies is proposed. Similar to the previous T-circuit based models, it is also developed based on equivalent T-circuit of the WPP induction generator. However, unlike in the previous models, the mathematical formulation of the new model is shorter and less complicated. Moreover, the derivation of the model in the present work is also much simpler. Only minimal mathematical operations are required in the process. Furthermore, the rotor voltage value of the WPP induction generator is readily available as an output of the proposed new model. This rotor voltage value can be used as a basis to calculate the induction generator slip. Validity of the new method is tested on a representative 9-bus electrical power system installed with WPP. Comparative studies between the proposed method (new model) and other method (previous model) are also presented